What do patients' efficacy and tolerability ratings of acute migraine medication tell us? Cross-sectional data from the DMKG Headache Registry. (May 2023) - Ruscheweyh, Ruth; Dresler, Thomas; Förderreuther, Stefanie; Gaul, Charly; Gossrau, Gudrun; Jürgens, Tim Patrick; Ruschil, Victoria; Straube, Andreas; Scheidt, Jörg
Background: Most migraine patients need an effective acute medication. Real-world data can provide important information on the performance of acute migraine medication in clinical practice. Methods: We used data from the German Migraine and Headache Society Headache Registry, where patients rate efficacy and tolerability of and satisfaction with each of their acute headache medications. Results: A total of 1756 adult migraine patients (females: 85%, age: 39.5 ± 12.8 years, headache days per month: 13.5 ± 8.1) were included. Of these, 93% used acute medication, most frequently triptans (59.3%) and/or non-opioid analgesics (56.4%), and 58.5% rated efficacy as good or very good. This was more frequent for triptans (75.4%) than for non-opioid analgesics (43.6%, p < 0.001). Among non-opioid analgesics, naproxen was rated most effective (61.9% very good or good, p < 0.001 compared to ibuprofen, acetylsalicylic acid and paracetamol). Patient-rated efficacy significantly declined with higher headache frequencies (p < 0.001), and this effect remained significant after omitting patients overusing acute medication. Conclusion: In the present population recruited at specialized headache centers, patients rated triptans as more effective than non-opioid analgesics, naproxen as more effective than ibuprofen, and acute medication efficacy decreased with increasing headache frequency. Trial registration: The German Migraine and Headache Society Headache Registry is registered with the German Clinical Trials Register (DRKS 00021081).